Invasive basal cell carcinoma: A case report - Figueirêdo Júnior, Ernani Canuto; Pereira, Maria do Socorro Vieira; Barsi Filho, Henrique Cezar Coutinho; Ferreira, Jadeilson de Moura; Xavier, Myllena Alves; Gomes, Daliana Queiroga de Castro; Pereira, Jozinete Vieira (ARCHIVES OF HEALTH INVESTIGATION, 2018)
Basal cell carcinoma (BCC) is an epithelial tumor of low-grade malignancy, recurrent, with capacity for local invasion and destruction of adjacent bone or cartilage, yet rare metastasis. It presents as superficial, fibro-epithelial, nodular, sclerosing or pigmented. The best treatment is surgical excision; and frequently the cancer has a good prognosis. The purpose of this article is to study and discuss the clinical, histopathological and treatment of BCC. Descriptors: Maxillofacial Abnormalities; Neoplasms; Carcinoma, Basal Cell; Diagnosis; Therapeutics.